Exploring empathy in cyberbullying with serious games - Costa Ferreira, P. A. N.; Veiga Simão, A. M.; Paiva, A.; Martinho, C.; Prada, R.; Ferreira, A. I.; Santos, F. (Computers and Education, 2021)
This study examined whether experiencing a multiplayer serious game could foster cognitive empathy in adolescent bystanders of cyberbullying, empathic concern for these situations and affective empathy towards those involved during game play. We also explored the players’ selfreflections about cyberbullying scenarios in the game. A quasi-experimental design was used. While participants in an alternative intervention group read the game’s storyline and filled in activities on paper, players in the experimental group interacted through a fictitious social network on themes related to organizing a school field trip and other activities. The control group had their regular classes. Quantitative (ANCOVA and Multilevel) and qualitative (Content analysis) results from 221 7th and 8th-graders recorded in classroom settings, showed that overall players reveal higher levels of cognitive empathy, empathic concern and affective empathy than those who did not play the game. Players referred appraisals and factual cognitions against cyberbullying, empathy towards the victim. Our game can help improve adolescents’ cognitive empathy and prosociality in cyberbullying.